Romanian Agriculture in the Context of the Post-2013 Common Agricultural Policy - Niculescu, Oana-Marilena (Mediterranean Journal of Social Sciences, 2012)
The European model of agriculture relies on the middle, usually typically family, farm. Romania does not fit this model, havingan unsuitable agricultural structure for a modern European state. The objective of this paper is to emphasize the differences between theEuropean model of agriculture and the Romanian agriculture. In Romania, the subsistence agriculture (many micro-farms, producing forself-consumption) and the agro-industrial agriculture (farms of hundreds even thousands of hectares, market oriented, relativelyadvanced), give a dual character to this important economic branch. The middle level agriculture is underdeveloped and uses only asmall percent of the agricultural area. The research method is the analysis of data; the study of the real convergence between theRomanian and the European Union’s agriculture implies a SWOT analysis.The main results reveal that the reform in the Romanianagriculture should include, among its priorities, the solving of the structural problem of the Romanian village, the development of themiddle level agriculture being an important aim. The implementation of the community regulations has to be accompanied by owndevelopment programs for the rural space and for the agro-food sector. Romania has to define its own strategy in order to be integratedin the community policy, strategy which must be sustained in the debates regarding the reform of the Common Agricultural Policy, thetarget being the development of the Romanian agriculture.